Putting Gender into Political Economy Analysis: why it matters and how to do it - and Brown, Emily; Haines, Rebecca; O’Neil, Tam (2018)
Gender specialists from Oxfam and Care introduce a new guide that covers both theory and practice of including gender in political economy analysis.
Keywords: Gender